PENYULUHAN TENTANG PEMBERIAN OBAT PIROXICAM PADA PASIEN YANG MENDERITA PENYAKIT REMATIK PADA USIA 50 TAHUN DI PUSKESMAS DELI TUA - Nerdy Nerdy (Jurnal Pengabdian Masyarakat Putri Hijau, 2020)
Introduction : Rheumatism is an autoimmune disease characterized by inflammation of the joints and can occur chronically. Patients will experience symptoms such as pain, inflammation, joint stiffness in the morning and difficulty moving. Piroxicam has biological activity as analgesic, anti-rheumatic and anti-inflammatory which is more or less the same as indomethacin, the working period of this drug is quite long with a dose of 10 to 20 mg a day. Piroxicam is well absorbed in the digestive tract, 99% of the drug is bound by plasma proteins. The increase in the population of the elderly has an impact on shifting disease patterns from infectious diseases to degenerative diseases, increasing age causes changes in the body of the elderly, one of which is the muscular system such as joints, bones and other skeletal muscles that put the elderly at risk of suffering from rheumatism. Lack of knowledge affects rheumatism management. The role of nurses in this case is to provide health education to the elderly and families to increase knowledge, willingness and ability of the elderly to live healthy. Objective: To be able to understand and know about Piroxicam Drug Administration in Patients with Rheumatic Disease at the Age of 50 Years. Methods: This counseling is carried out interactively between the presenters and the participants so that it is necessary to provide further understanding of the concern about the administration of Piroxicam medicine to patients suffering from rheumatic disease at the age of 50 years. Result : The extension activity was able to increase the participants' knowledge at Puskesmas Deli Tua. Conclusion: the extension activity has been able to increase the participants' knowledge at the Puskesmas Deli Tua and the participants can understand about the administration of piroxicam medicine to patients suffering from rheumatism at the age of 50 years.